Investigation of the permeability and selectivity of gases and volatile organic compounds for polydimethylsiloxane membranes - De Bo, Inge; Van Langenhove, Herman; Pruuost, Peter; De Neve, Jeroen; Pieters, Jan; Vankelecom, Ivo F.J; Dick, Erik (Journal of membrane science, 2003)
Selectivity of oxygen, carbon dioxide, ethylene, dimethyl sulphide, trichloroethylene and toluene from air and their permeability ( P) and diffusivity ( D m) are reported for a polydimethylsiloxane (PDMS) membrane at 30 °C. All are constants within the studied feed concentration interval (0.04–233 g m −3). The presence of oxygen in the vapour/air mixtures has no significant influence on the vapour permeation. All resistances for mass transfer are determined in the PDMS membrane while gas phase resistances are negligible. Increasing feed concentration or decreasing membrane thickness results in a linear increase of the compound’s permeation. Computer simulations of the permeation tests indicate that the concentration in the permeate stream along the membrane sheet can be approximated by a logarithmic concentration profile. The highest permeability and lowest diffusivity are found for toluene, followed by trichloroethylene, dimethyl sulphide, ethylene, carbon dioxide and oxygen. Ratios between lowest and highest value for P and D m were 300 and 11, respectively. The relative high selectivity of vapours compared to oxygen can hinder an optimal bioreactor operation for breaking down gaseous pollutants when a PDMS membrane is used as gas/liquid contactor. In some cases, it is expected that unsufficient amounts of oxygen permeate for complete metabolisation of the pollutants.